P4.07 EFFECTS OF ANTI-HYPERTENSIVE TREATMENT ON FUNCTIONAL AND STRUCTURAL COMPONENTS OF LARGE ARTERY STIFFNESS IN A RODENT MODEL OF TYPE I DIABETES - E. Salum; A.P. Avolio; J. Kals; P. Kampus; M. Butlin (Artery Research, 2013)
Objectives: Diabetes is associated with cardiovascular risk and increased arterial stiffness. Whether large artery stiffness is associated with diabetes per se or concomitant hypertension is currently unknown. Methods: Male, Wistar rats (6 weeks) were divided into control (n=8), control with anti-hypertensive treatment (telmisartan, 10mg/kg/day, n=8), induced diabetes (intraperitoneal streptozotocin, 50 mg/kg, confirmed by blood glucose measurement, n=12) and diabetes with anti-hypertensive treatment (n=12). At 18 weeks, rats were anaesthetised (urethane, 1.3 g/kg) and aortic pulse wave velocity (aPWV, aortic stiffness) measured invasively across a full range of physiological arterial pressure (intravenous phenylephrine, sodium nitroprusside, 30 μg/kg/min). Passive (elastin, collagen) and active (endothelial, smooth muscle function) components of stiffness were quantified using tensile testing and myography. Results: Conscious, systolic blood pressure was high in both control and diabetic animals (142±16, 132±22 mmHg) compared to control and diabetic animals on anti-hypertensive therapy (105±11, 119±14 mmHg, p<0.01). Diabetic animals had marginally but significantly lower aPWV across all pressures (Figure). Anti-hypertensive treatment increased aPWV in controls and diabetic animals, but increased the pressure dependency of aPWV (Figure). There was no difference in endothelial dependent or independent vasorelaxation. Sensitivity to phenylephrine (vasoconstriction) was less in diabetic animals (p<0.05). Anti-hypertensive therapy caused a rightward shift in the aortic stress-strain curve (p<0.001). Conclusions: Diabetes appeared to have a small but positive effect on arterial stiffness when studied independent of blood pressure. However, high blood pressure decreased the artery’s ability to respond to acute pressure changes, possibly due to remodelling of passive aortic wall components.